Prophylactic nasal continuous positive airways pressure in newborns of 28–31 weeks gestation: multicentre randomised controlled clinical trial. Issue 5 (20th August 2004) - Sandri, F; Ancora, G; Lanzoni, A; Tagliabue, P; Colnaghi, M; Ventura, M L; Rinaldi, M; Mondello, I; Gancia, P; Salvioli, G P; Orzalesi, M; Mosca, F
Abstract : Background: The role of nasal continuous positive airways pressure (nCPAP) in the management of respiratory distress syndrome in preterm infants is not completely defined. Objective: To evaluate the benefits and risks of prophylactic nCPAP in infants of 28–31 weeks gestation. Design: Multicentre randomised controlled clinical trial. Setting: Seventeen Italian neonatal intensive care units. Patients: A total of 230 newborns of 28–31 weeks gestation, not intubated in the delivery room and without major malformations, were randomly assigned to prophylactic or rescue nCPAP. Interventions: Prophylactic nCPAP was started within 30 minutes of birth, irrespective of oxygen requirement and clinical status. Rescue nCPAP was started when Fio 2 requirement was > 0.4, for more than 30 minutes, to maintain transcutaneous oxygen saturation between 93% and 96%. Exogenous surfactant was given when Fio 2 requirement was > 0.4 in nCPAP in the presence of radiological signs of respiratory distress syndrome. Main outcome measures: Primary end point: need for exogenous surfactant. Secondary end points: need for mechanical ventilation and incidence of air leaks. Results: Surfactant was needed by 22.6% in the prophylaxis group and 21.7% in the rescue group. Mechanical ventilation was required by 12.2% in both the prophylaxis and rescue group. The incidence of air leaks was 2.6% in both groups. More than 80% of both groups had received prenatal steroids. Conclusions: In newborns of 28–31 weeks gestation, there is no greater benefit in giving prophylactic nCPAP than in starting nCPAP when the oxygen requirement increases to a Fio 2 > 0.4.